A comparison of selected breed crosses on growth rate during long-term grazing - Riley, Jack G.; Pope, Ronald V. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Brahman crossbred and Simmental crossbred calves gained similarly during a 312-day, native range grazing study. Longhorn crossbreds gained less than the Brahman or Simmental crosses but more than the British crossbreds, which served as controls. Most of the gain advantage was obtained during the summer portion (April 30-September 20) of the project.
Keywords: Beef; Growth rate; Grazing; Crossbreds